Comparative bark anatomy of drought tolerant and susceptible clones of Hevea brasiliensis - Premakumari D; Marattukalam J G; Panikkar A O N; Sethuraj M R (Indian Journal of Natural Rubber Rsearach, 1993)
In the Para rubber tree summer drop in yield is observed in many cultivars. This is a clonal characteristic mediated through latex flow pattern, which in turn is governed by several other factors. As structural parameters have strong bearing on clonal performance, a study was made to compare some drought tolerant and susceptible clones for bark anatomical characters. Six clones, three showing drought susceptibility and the other three drought tolerance, were chosen for the study. Significant clonal differences were recorded for the proportion of soft bast (P<0.01), total number of latex vessel rows (P<0.05), proportion of latex vessel rows in the soft bast region (P<0.01>, height of pholic rays (P,o.01), width of pholic rays (P<0.01) and height to width ratio of pholic rays (P<0.01). Significant differences between drought tolerant and susceptible groups of clones were recorded for the proportion of soft bast, proportion of latex vessel rows in the soft bast region, width of pholic rays and height to width ratio of pholic rays. Importance of tolerance have been discussed in the light of theoretical considerations and functional possibilities.
Keywords: Bark anatomy; Drought tolerance; Hevea brasiliensis; India